Theoretical Study of Interaction Between Thiadiazole Derivatives on Fe(110) Surface - Thomas Nyijime; Habibat Chahul; Abdullahi Ayuba; FATER IORHUNA (Journal of Chemistry Letters)
The theoretical performance of 4-methoxyphenyl-1,3,4-thiadiazole (AMPT), 2-Amino-5-(4-chlorophenyl)-1,3,4-thiadiazole (ACPT) and 2-amino-5-phenyl-1,3,4-thiadiazole (APT) as inhibitors of iron corrosion was assessed with a view of determining the mechanism of the inhibition process. The reactivity of the molecules with the computed descriptors was explored in order to define and correlate calculations that take into account a number of several global descriptors. Results obtained by calculating adsorption or binding energies were in good agreement with the experimentally reported results elsewhere. Regarding the computed adsorption or binding energies, their generally low values inferred that the compounds are poorly adsorbed onto the surface of Fe through Van der Waals forces and as a result obey the mechanism of physical adsorption. In order to analyze local reactivity parameters, first- and second-order condensed Fukui functions were used. Simulations involving the adsorbed molecules on Fe (1 1 0) surface were carried out through quench dynamic simulations, and the mechanism of physical adsorption was established with 4-methoxyphenyl-1,3,4-thiadiazole (AMPT), which has proven to be a more effective inhibitor on the Fe surface than 2-amino-5-(4-chlorophenyl)-1,3,4-thiadiazole and 2-Amino-5-phenyl-1,3,4-thiadiazole (APT). Fukui indices values revealed that the active sites were found to be located on the molecules heteroatoms (Sulphur and Nitrogen).